The mediating effect of information and communication technology utilization on cognitive function and activities of daily living in eldery with cognitive decline - Lee, Jee Young (Edelweiss Applied Science and Technology, 2025)
This study aimed to identify the mediating effect of information and communication technology (ICT) utilization on cognitive function and activities of daily living (ADL) / instrumental activities of daily living (IADL) in Korean elderly individuals with cognitive decline. A total of 2,448 individuals aged 65 and older with cognitive decline were selected as study subjects from the original dataset of the 2023 National Survey on the Status of the Elderly. The data were analyzed using SPSS/WIN 25.0 with a complex sample analysis method. Frequency and descriptive statistics, partial correlation analysis, general linear model analysis, and Sobel’s test were performed. The results showed a negative correlation between cognitive function and ADL/IADL, and a positive correlation between cognitive function and ICT utilization. ICT utilization was shown to be negatively correlated with ADL/IADL. Results also indicated that ICT utilization partially mediates the relationship between cognitive function and ADL/IADL. These findings suggest that using ICT can be a preventive factor in reducing the ability to perform daily activities that can be attributed to cognitive decline. This implies that we should consider strategies to strengthen the use of ICT that affect the maintenance and improvement of daily life performance for older adults with cognitive decline.